STUDENTS SPEAKING SKILL UTILIZING SHORT MOVIE THE PRESENT AT SMA NEGERI 1 KOTA TERNATE - Cantika Islamiati Zainuddin; Roswita M. Aboe; Agus Supriyadi (Cakrawala Bahasa, 2022)
The objective of this research is to find out the students' speaking skill through the medium of animated short movie that will retold by students. The sample of this research was 20 students from X grade of SMA Negeri 1 Ternate City. The method in this research was mixed method. The instrument used in this research was a short movie entitled "The Present". The data were analyzed by using the speaking scoring rubric by calculating student scores individually and looking for the total score. The data was presented in the form of descriptions, tables and graph. Based on the results obtained from the research, the speaking ability of X grade students of SMA Negeri 1. Ternate City is in Average level with the total score was 52. The results score of students' abilities in the grammatical aspect of speaking was 47, in the vocabulary aspect was 55, on the comprehension aspect was 58, on the fluency aspect was 52, and on the pronunciation aspect was 48. Based on these results, it is suggested that students should practice speaking in English both outside and inside the classroom in order to improve their ability to understand and master the aspects of speaking English. Teachers are advised to pay more attention to students' speaking skills and provide opportunities for students by creating various interesting activities that allow students to practice their speaking skills in English.